"CONFINED" TEACHING AND ICT AT THE UNIVERSITY: WHAT REPRESENTATIONS TO A GROUP OF STUDENTS FROM THE ENSB (ALGIERS)? - Assia BELGHEDDOUCHE (Universitaria Publishing House, Craiova, 2020)
The coronavirus crisis has affected all countries and has changed the daily lives of millions of people, including teachers and learners around the world. They have been hit hard by this crisis and have undergone changes in their teaching / learning practices. In this work, we will try to question the representations and opinions of a group of students from the ENSB (L'École Normale Supérieure de Bouzaréah) in Algiers while they are still experiencing these upheavals because we think that these representations will have an influence on their current and future practices. Our goal is to collect their perceptions of online and distance education during confinement, and to learn about the teaching practices that they believe have helped or hindered their learning. We will also try to see if these perceptions influence their intention to use ICT in their future practice as teachers.